Liquid crystal polymer powder, liquid crystal polymer film, and manufacturing method thereof

JP7639987B2Active Publication Date: 2025-03-05MURATA MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024508784
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-27
Filing Date
2023-05-22
Publication Date
2025-03-05
Estimated Expiration
2043-05-22

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、液晶ポリマーフィルムの耐折強度を向上できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639987000005
    Figure 0007639987000005
  • Figure 0007639987000006
    Figure 0007639987000006
  • Figure 0007639987000007
    Figure 0007639987000007
Patent Text Reader

Abstract

Provided is a liquid crystal polymer film having improved folding endurance. The liquid crystal polymer powder comprises fibrous particles formed from a liquid crystal polymer. The melt viscosity of the liquid crystal polymer powder is 15 to 77 Pa•s.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid crystal polymer powder, a method for producing a liquid crystal polymer powder, a liquid crystal polymer film, and a method for producing a liquid crystal polymer film. [Background technology]

[0002] In recent years, liquid crystal polymers (LCPs), which have less transmission loss and excellent high-frequency characteristics compared to conventional materials, have been attracting attention as a new substrate material for printed wiring compatible with next-generation high-speed transmission. Compared to polyimide resin, a conventional substrate material, LCPs have excellent low dielectric constant characteristics, high heat resistance, and low water absorption, which allows them to reduce loss of electrical signals, etc.

[0003] Known methods for producing LCP films from liquid crystal polymers for use in printed wiring boards and the like include, for example, melt extrusion and solution casting. The melt extrusion method is a method in which a film is formed by extruding molten resin from an apparatus and contacting it with a roll. The solution casting method is a method in which a varnish made by dissolving LCP raw materials such as LCP pellets in a solvent is applied onto a flat belt and dried to form an LCP film.

[0004] On the other hand, Patent Document 1 describes a method for producing a fibril-like liquid crystal polymer powder. In this method, first, a biaxially oriented film of a liquid crystal polymer is pulverized to obtain a liquid crystal polymer (LCP) powder. Next, the obtained LCP powder is treated using a wet high-pressure crushing device to produce a fibril-like LCP powder. Such a fibril-like LCP powder can also be used as a raw material to produce an LCP film. It is considered that the folding endurance of the LCP film is improved due to the improved bonding between the fibril-like LCP particles after drying.

[0005] Patent Document 2 (JP Patent Publication 5-125160 A) discloses a resin composition exhibiting liquid crystallinity composed of two types of segments, and describes that the resin composition has a small temperature dependency of melt viscosity characteristics, is excellent in moldability, and can be used to obtain molded products of good shape (sheets with uniform thickness). Patent Document 2 describes that the resin composition is melted at a temperature of 245° C. and a shear rate of 1000 per second (sec -1 ) is described as having a melt viscosity of 800 poise (80 Pa s) or more. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 5904307 [Patent Document 2] Japanese Patent Application Publication No. 5-125160 Summary of the Invention [Problem to be solved by the invention]

[0007] When a liquid crystal polymer film is used for a substrate for a printed wiring, for example, it is desirable that the film has a high folding endurance in order to improve the reliability of the printed wiring. In particular, when the film is used for a substrate for a flexible printed wiring, the film is required to have a high folding endurance. For this reason, there is room for further improvement in the folding endurance of conventional liquid crystal polymer films.

[0008] In view of the above problems, an object of the present invention is to provide a liquid crystal polymer film having improved folding strength. [Means for solving the problem]

[0009] A liquid crystal polymer powder according to a first aspect of the present invention contains fibrous particles made of a liquid crystal polymer. The liquid crystal polymer powder has a melt viscosity of 15 to 77 Pa·s.

[0010] A liquid crystal polymer film according to a second aspect of the present invention includes a liquid crystal polymer. The liquid crystal polymer film has an MIT folding endurance of 100 or more. Effect of the Invention

[0011] According to the present invention, the folding endurance of the liquid crystal polymer film can be improved. [Brief description of the drawings]

[0012] [Figure 1] 2 is a photograph of liquid crystal polymer powders in Comparative Example 1 and Examples 1 to 9. [Diagram 2] FIG. 2 is a diagram showing the relationship between the melt viscosity and the bulk density of liquid crystal polymer powders in Examples and Comparative Examples. [Diagram 3] FIG. 2 is a diagram showing the relationship between the melt viscosity of a liquid crystal polymer powder and the folding endurance (MIT folding endurance number) of a liquid crystal polymer film in Examples and Comparative Examples. [Figure 4] FIG. 2 is a diagram showing the relationship between the melt viscosity of a liquid crystal polymer powder and the coefficient of linear expansion (CTE) of a liquid crystal polymer film in Examples and Comparative Examples. [Diagram 5] FIG. 2 is a flow diagram showing a manufacturing process of a liquid crystal polymer powder according to an embodiment. [Figure 6] FIG. 2 is a flow diagram showing a manufacturing process of the liquid crystal polymer film of the embodiment. [Figure 7] FIG. 2 is a flow diagram showing a manufacturing process of a fiber mat according to an embodiment. [Figure 8] FIG. 2 is a diagram showing a matting step for matting liquid crystal polymer powder in the process for producing a fiber mat. [Figure 9] FIG. 13 is a diagram showing a process of irradiating a second surface of the fiber mat with light. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] A liquid crystal polymer powder and a liquid crystal polymer film according to one embodiment of the present invention will be described below.

[0014] <Liquid crystal polymer powder> A liquid crystal polymer (LCP) powder according to one embodiment of the present invention contains fibrous particles made of a liquid crystal polymer.

[0015] The liquid crystal polymer is, for example, a thermotropic liquid crystal polymer. The molecules of the liquid crystal polymer have a negative linear expansion coefficient (coefficient of thermal expansion: CTE) in the axial direction of the molecular axis, and a positive CTE in the radial direction of the molecular axis. It is preferable that the liquid crystal polymer does not have an amide bond.

[0016] Examples of thermotropic liquid crystal polymers that do not have amide bonds include copolymers of parahydroxybenzoic acid, terephthalic acid, and dihydroxybiphenyl (block copolymers of parahydroxybenzoic acid and ethylene terephthalate) that have a high melting point and a low CTE and are called type 1 liquid crystal polymers, and copolymers (block copolymers) of parahydroxybenzoic acid and 2,6-hydroxynaphthoic acid that have a melting point between type 1 liquid crystal polymers and type 2 liquid crystal polymers and are called type 1.5 (or type 3) liquid crystal polymers.

[0017] (Melt Viscosity) The melt viscosity of the liquid crystal polymer powder is 15 to 77 Pa·s, preferably 20 to 77 Pa·s. This allows the fibrous particles constituting the liquid crystal polymer powder to have a large aspect ratio (long fibers), and the folding strength of the liquid crystal polymer film produced using the liquid crystal polymer powder can be improved. Furthermore, the fiber mat produced using the liquid crystal polymer powder can have an improved breaking tension even if the heat treatment temperature is equal to or lower than the melting point of the liquid crystal polymer raw material. In addition, by setting the heat treatment temperature to equal to or lower than the melting point of the liquid crystal polymer raw material, the porosity of the fiber mat can be adjusted.

[0018] It is believed that the higher the melt viscosity of the LCP, the higher the molecular weight of the LCP. When the molecular weight of the LCP is high, the proportion of defects between the polymers (LCP molecules) is low. It is believed that the influence of the molecular weight and proportion of defects of the LCP makes the LCP fibers (fibrous particles) in the LCP powder produced from the LCP raw material by the method described below long, and that the proportion of powder with a small aspect ratio decreases, resulting in an increase in the proportion of fibrous particles. This is believed to lower the CTE of the LCP film and improve its strength. In addition, liquid crystal polymer powder with a melt viscosity of more than 80 Pa·s is difficult to actually prepare because the viscosity of the original LCP raw material is too high and there is a tendency for small amounts of foreign matter to be generated at the discharge outlet during pelletization.

[0019] The melt viscosity of the liquid crystal polymer powder is more preferably 30 to 70 Pa s. In this case, the fibrous particles constituting the LCP powder have a larger aspect ratio (longer fibers), and the linear expansion coefficient of the LCP film produced using the LCP powder can be reduced.

[0020] The melt viscosity of the liquid crystal polymer powder is measured by a Capillograph manufactured by Toyo Seiki Seisakusho Co., Ltd. under the following measurement conditions in accordance with JIS K7199. Temperature: Melting point of liquid crystal polymer + 25℃) Shear rate: 1000 sec -1 Capillary: Length 20mm / Diameter 1mm

[0021] Although the above-mentioned Patent Document 2 refers to the relationship between the melt viscosity of LCP and moldability, it does not mention anything about the melt viscosity of LCP and the mechanical properties of LCP molded products.

[0022] By having a melt viscosity of 15 to 77 Pa·s or more, the fibrous particles that make up the liquid crystal polymer powder have a large aspect ratio (long fiber shape) and the average fiber thickness becomes thinner. As a result, the fibers become more physically entangled, and because the fiber diameter is also thin, they melt and bond at a lower temperature. Therefore, it is thought that the strength of the fiber mat will improve even when heated below the melting point of the liquid crystal polymer raw material. The reason why thinner fibers melt at a lower temperature is that the thinner fibers have a higher surface area in their volume, and as a result, they have low crystallinity and melt at a lower temperature. Since the crystals have a regular structure, it is thought that they are less present in areas such as the surface where bonds are broken and the degree of freedom is increased.

[0023] (fibrous particles) The fibrous particles contained in the LCP powder are not particularly limited as long as they contain a fibrous portion. The fibrous portion may be linear or may have branches.

[0024] The average aspect ratio of the fibrous particles is preferably 10 or more and 500 or less, more preferably 300 or less, and even more preferably 100 or less. The average diameter of the fibrous particles is more preferably 2 μm or less, and more preferably 1 μm or less. Such an LCP powder containing fine fibrous particles cannot be produced by a conventional method. For example, ultrafine fibers made of LCP obtained by cutting continuous LCP long fibers produced by a conventional electrospinning method usually have an aspect ratio of more than 500.

[0025] The average diameter and average aspect ratio of the fibrous particles contained in the LCP powder are measured by the following method.

[0026] (Measurement of the average diameter and average aspect ratio of fibrous particles) The LCP powder to be measured is dispersed in ethanol to prepare a slurry containing 0.01% by mass of LCP powder. At this time, the slurry is prepared so that the water content in the slurry is 1% by mass or less. Then, 5 to 10 μL of this slurry is dropped onto a slide glass, and the slurry on the slide glass is allowed to dry naturally. By allowing the slurry to dry naturally, the LCP powder is placed on the slide glass. Next, a predetermined area of ​​the LCP powder placed on the slide glass is observed with a scanning electron microscope to collect 100 or more pieces of image data of the particles constituting the LCP powder. In collecting the image data, the area is set according to the size of each LCP particle so that the number of image data is 100 or more. In order to prevent the occurrence of missed image data collection or measurement errors for each particle of the LCP, the magnification of the scanning electron microscope is appropriately changed to 500x, 3000x, or 10000x to collect the image data. Next, using the collected image data, the longitudinal dimension and width dimension of each particle of the LCP powder are measured. The direction of the straight line connecting both ends of the longest path among the paths that can be taken on one particle of the LCP powder captured in each of the image data, i.e., the path that passes through approximately the center of the particle from one end to the opposite end of the particle, is defined as the longitudinal direction. The length of the straight line connecting both ends of the longest path is measured as the longitudinal dimension. In addition, the particle size in the direction perpendicular to the longitudinal direction is measured at three different points in the longitudinal direction of each particle of the LCP powder, and the average value of the dimensions measured at these three points is defined as the width direction dimension (fiber diameter) per particle of the LCP powder. Furthermore, the ratio of the longitudinal dimension to the fiber diameter [longitudinal dimension / fiber diameter] is calculated to obtain the aspect ratio of the fibrous particle. The average value of the fiber diameters measured for 100 fibrous particles is taken as the average diameter. The average aspect ratio is determined as the average value of the aspect ratios measured for 100 fibrous particles.

[0027] The fibrous particles may be contained in the LCP powder as aggregates of the fibrous particles.

[0028] In addition, the axial direction of the LCP molecules constituting the fibrous particles tends to coincide with the longitudinal direction of the fibrous particles. When an LCP powder is produced through a fiberization process described below, it is believed that the axial direction of the LCP molecules is aligned along the longitudinal direction of the fibrous particles due to breakage between multiple domains formed by bundling the LCP molecules.

[0029] The bulk density of the LCP powder is preferably 2 to 5 mg / cm. 3 and more preferably 2.5 to 4.5 mg / cm 3 and more preferably 2.5 to 4 mg / cm 3 It is.

[0030] In the LCP powder, the content (number ratio) of particles other than fibrous particles (aggregated particles that are not substantially fibrous) is preferably 20% or less. For example, when the LCP powder is placed on a flat surface, particles with a maximum height of 10 μm or less are fibrous particles, and particles with a maximum height of more than 10 μm are aggregate particles.

[0031] The LCP powder preferably has a D50 (average particle size) value of 13 μm or less, as measured by particle size measurement using a particle size distribution measuring device based on a laser diffraction scattering method.

[0032] The melting point of the LCP is preferably more than 300°C, and more preferably more than 330°C. The "melting point" here means the "endothermic peak temperature" measured using a differential scanning calorimeter while heating the LCP to 400°C in an inert atmosphere, cooling it to room temperature at a temperature drop rate of 40°C / min or more, and heating it again at a temperature rise rate of 40°C / min. When the melting point (endothermic peak temperature) of the LCP is more than 300°C, an LCP film with excellent heat resistance can be obtained. In addition, when the LCP film is used as a circuit board, damage to the circuit board during repair using a soldering iron can be suppressed. The melting point of the LCP powder is usually 1 to 3°C lower than the melting point of the liquid crystal polymer raw material.

[0033] From the viewpoint of forming an LCP film, the melting point of the LCP is preferably lower than the decomposition temperature of the LCP, for example, 400° C. or lower.

[0034] The liquid crystal polymer powder may further contain a zirconium compound. The zirconium compound is preferably contained in an amount of 0.001% by weight or more and 0.1% by weight or less, more preferably 0.003% by weight or more and 0.05% by weight or less, based on the total amount of the liquid crystal polymer powder. By containing a small amount of zirconium compound, when light is irradiated in a subsequent processing step, the light irradiation efficiency can be increased due to the light absorption characteristics of the zirconium compound.

[0035] The zirconium compound refers to a compound containing a zirconium atom. Examples of the zirconium compound include zirconium acetate, zirconium hydroxide, and zirconium oxide, and among them, zirconium dioxide (zirconia) is preferably used. The zirconium compound contained in the liquid crystal polymer powder is preferably particulate, and the particle size is preferably 1 nm or more and 500 μm or less, more preferably 10 nm or more and 100 nm or less. It is assumed that the zirconium compound is mixed with the one used as a medium when crushing the coarsely crushed liquid crystal polymer during the manufacturing process of the liquid crystal polymer powder.

[0036] <Liquid crystal polymer film> A liquid crystal polymer (LCP) film according to one embodiment of the present invention comprises a liquid crystal polymer.

[0037] The LCP film of the present embodiment preferably has an MIT folding endurance number of times of 100 or more. The MIT folding endurance number is the number of times that a test film is required to be bent to break when a test film having a width of 10 mm and a thickness of 25 μm taken from the LCP film is subjected to an MIT folding fatigue test under conditions of a load of 500 g, a curvature radius of 0.2 mm, a bending angle of 135 degrees, and a bending speed of 175 cpm.

[0038] Thus, an LCP film having an MIT folding endurance of 100 or more can be suitably used as a substrate for a flexible printed circuit (FPC), a vibration plate, an organic semiconductor substrate, an organic EL substrate, a vibration damper, etc. In other words, the LCP film according to the present embodiment preferably has excellent folding endurance from the viewpoint of being applicable to the above-mentioned substrates, etc.

[0039] The linear expansion coefficient of the LCP film in the plane (XY direction) is preferably 20 ppm / ° C. or less, and more preferably 18 to 20 ppm / ° C. The linear expansion coefficient of the LCP film is the linear expansion coefficient of the LCP film in the plane (XY direction) measured by a TMA (thermomechanical analysis) method in accordance with JIS K 7197. The conditions of the TMA method are heating from room temperature to 150° C. at a rate of 10° C. / min in a nitrogen atmosphere, a load of 10 g, and a rectangular shape of the sample (5 mm×15 mm).

[0040] The thickness of the LCP film is preferably, for example, 5 μm or more and 250 μm or less.

[0041] The LCP film preferably has a water absorption rate of 0.2% by mass or less when immersed in water at room temperature for 24 hours. Thus, if the water absorption rate is 0.2% by mass or less, the LCP film can be more suitably used as a high-frequency circuit board member. If an LCP film having a water absorption rate of 0.2% by mass or less is used as a high-frequency circuit board member, the high-frequency circuit board is prevented from containing water with an extremely high dielectric constant, and an increase in dielectric loss due to an increase in the relative dielectric constant and dielectric loss tangent can be suppressed, and further, the occurrence of inconsistency in characteristic impedance due to a change in the dielectric constant and the associated transmission loss can be suppressed. For example, an LCP film made of a liquid crystal polymer having an amine-derived structure introduced into its molecular structure has a relatively high water absorption rate, and therefore has a water absorption rate of more than 0.2% by mass.

[0042] The LCP film according to the present embodiment may have copper foil bonded to at least one surface, or may have copper foil bonded to both surfaces. In this case, the LCP film according to the present embodiment may be used as a laminated molded product, for example, as FCCL (Flexible Copper Clad Laminates) that allows circuit formation by a subtractive method.

[0043] <Fiber mat> The fiber mat according to one embodiment of the present invention includes a liquid crystal polymer. The breaking tension of the fiber mat of this embodiment is preferably 0.8 N / 20 mm or more, more preferably 1.0 N / 20 mm or more. The breaking tension of the fiber mat may be 1.2 N / 20 mm or more, or may be 1.5 N / 20 mm or more. According to the present invention, even when the heat treatment is performed at a temperature below the melting point of the liquid crystal polymer, the breaking tension can be improved compared to the fiber mat before the heat treatment, and a fiber mat having a breaking tension of 1.0 N / 20 mm or more can be obtained.

[0044] The breaking tension of the fiber mat can be measured using an autograph (AG-XDplus, manufactured by Shimadzu Corporation). In this case, the width of the fiber mat at the time of measurement is 20 mm.

[0045] The overall basis weight of the fiber mat is approximately 30-40 g / m 2 The overall density of the fiber mat is, for example, 0.30 to 0.60 g / m 3 and the density increases as the fused area of ​​the liquid crystal powder polymer in the thickness direction increases.

[0046] The thickness of the fiber mat is approximately 50 to 100 μm, and the thickness decreases as the fused region of the liquid crystal powder polymer in the thickness direction becomes larger.

[0047] <<Methods of manufacturing liquid crystal polymer powder, liquid crystal polymer film and fiber mat>> Hereinafter, a method for producing a liquid crystal polymer powder and a liquid crystal polymer film according to one embodiment of the present invention will be described.

[0048] <Method of manufacturing liquid crystal polymer powder> As shown in FIG. 5, the method for producing a liquid crystal polymer powder according to this embodiment includes a coarse pulverization step (S11), a fine pulverization step (S12), a coarse particle removal step (S13), and a fiberization step (S14) in this order.

[0049] (Preparation of LCP raw materials) In the method for producing a liquid crystal polymer powder according to the present embodiment, first, a raw material made of a liquid crystal polymer (LCP raw material) is prepared.

[0050] Examples of the LCP raw material include a uniaxially oriented pellet-shaped liquid crystal polymer, a biaxially oriented film-shaped liquid crystal polymer, or a powder-shaped liquid crystal polymer. From the viewpoint of production cost, a pellet-shaped or powder-shaped liquid crystal polymer is preferable because it is less expensive than a film-shaped liquid crystal polymer, and a pellet-shaped liquid crystal polymer is more preferable. In this embodiment, the LCP raw material does not include a liquid crystal polymer directly formed into a fiber shape by an electrospinning method or a melt-blowing method. However, the LCP raw material may include a liquid crystal polymer processed into a fiber shape by crushing a pellet-shaped liquid crystal polymer or a powder-shaped liquid crystal polymer.

[0051] The melt viscosity of the LCP raw material is 15 to 79 Pa·s, and preferably 20 to 79 Pa·s. The melt viscosity of the LCP raw material is basically the same as the melt viscosity of the liquid crystal polymer powder constituting the fibrous particles contained in the above-mentioned LCP powder.

[0052] The melting point of the LCP raw material is preferably higher than 300° C., more preferably higher than 330° C., and even more preferably equal to or higher than 350° C. This makes it possible to obtain a liquid crystal polymer film having excellent heat resistance, which contains a liquid crystal polymer having a melting point of more than 300° C.

[0053] When the melting point of the LCP raw material is higher than 300°C, the LCP raw material is preferably a pellet-shaped or powder-shaped liquid crystal polymer. A film-shaped liquid crystal polymer is usually formed by melt extrusion. However, when attempting to form a film-shaped liquid crystal polymer by melt extrusion using a liquid crystal polymer with a melting point higher than 300°C, a large amount of fish eyes of the liquid crystal polymer are generated or degradation due to decomposition occurs. This is because when attempting to form a film-shaped liquid crystal polymer by melt extrusion using a liquid crystal polymer with a melting point higher than 300°C, it is necessary to heat the liquid crystal polymer to near its decomposition temperature and continuously knead it.

[0054] (Coarse grinding process: S11) In the coarse pulverization step, the LCP raw material is coarsely pulverized. For example, the LCP raw material is coarsely pulverized with a cutter mill. The size of the coarsely pulverized LCP particles is not particularly limited as long as it can be used as a raw material for the fine pulverization step described later. The maximum particle size of the coarsely pulverized LCP particles is, for example, 3 mm or less.

[0055] The method for producing an LCP film in this embodiment does not necessarily have to include a coarse pulverization step. For example, if the LCP raw material can be used as a raw material for the fine pulverization step, the LCP raw material may be used directly as a raw material for the fine pulverization step. However, if the melting point of the LCP raw material is higher than 330°C, it is preferable to carry out the coarse pulverization step before the subsequent fine pulverization step. In the coarse pulverization step, it is preferable to carry out coarse pulverization in a high-pressure dispersed state. The number of dispersion treatments is preferably 1 to 50 times, more preferably 1 to 10 times. By carrying out pulverization by high-pressure dispersion in the coarse pulverization step, it becomes easier to obtain a granular finely pulverized liquid crystal polymer in the subsequent step.

[0056] (Fine grinding process: S12) In the fine pulverization step, the LCP raw material (after the coarse pulverization step) is pulverized while being dispersed in liquid nitrogen to obtain granular finely pulverized liquid crystal polymer (finely pulverized LCP).

[0057] In the pulverization step, it is preferable to pulverize the LCP raw material dispersed in liquid nitrogen using media. The media is, for example, beads. For example, zirconia particles can be used as the media. The particle size of the zirconia used as the media is preferably 0.1 mm or more and 10 mm or less, more preferably 1 mm or more and 8 mm or less. In the pulverization step of this embodiment, it is preferable to use a bead mill, which has relatively few technical problems, from the viewpoint of handling liquid nitrogen. An example of a device that can be used in the pulverization step is the liquid nitrogen bead mill "LNM-08" manufactured by Imex.

[0058] In the fine pulverization process of this embodiment, the pulverization method of pulverizing the liquid crystal polymer in a state of being dispersed in liquid nitrogen is different from the conventional freeze pulverization method. The conventional freeze pulverization method is a method of pulverizing the raw material to be pulverized while pouring liquid nitrogen onto the raw material to be pulverized and the main body of the pulverization device, but most of the liquid nitrogen has evaporated at the time the raw material to be pulverized is pulverized. In other words, in the conventional freeze pulverization method, most of the raw material to be pulverized is not dispersed in liquid nitrogen at the time the raw material to be pulverized is pulverized.

[0059] In the conventional freeze-pulverization method, the heat of the raw material to be pulverized itself, the heat generated by the pulverization device, and the heat generated by the pulverization of the raw material to be pulverized vaporize the liquid nitrogen in an extremely short time. Therefore, in the conventional freeze-pulverization method, the raw material being pulverized inside the pulverization device is at a temperature much higher than the boiling point of liquid nitrogen, which is -196°C. In other words, in the conventional freeze-pulverization method, pulverization is performed under conditions where the temperature inside the pulverization device is usually between -100°C and 0°C. In the conventional freeze-pulverization method, even if as much liquid nitrogen as possible is supplied, the temperature inside the pulverization device is at its lowest about -150°C.

[0060] For this reason, when, for example, a uniaxially oriented pellet-shaped liquid crystal polymer (or a coarsely pulverized product thereof) is pulverized in the conventional freeze-pulverization method, the pulverization proceeds along a plane approximately parallel to the axial direction of the molecular axis of the liquid crystal polymer, and it is considered that a fibrous liquid crystal polymer having a very large aspect ratio and a fiber diameter far larger than 3 μm is obtained. In other words, even if a uniaxially oriented pellet-shaped liquid crystal polymer is pulverized by the conventional freeze-pulverization method, it is not possible to obtain a granular finely pulverized liquid crystal polymer as used in this embodiment.

[0061] In this embodiment, the raw material to be pulverized is pulverized in a state dispersed in liquid nitrogen, so that the raw material is pulverized in a state that is even more cooled than in the conventional freeze-pulverization method. Specifically, the raw material to be pulverized is pulverized at a temperature lower than −196° C., which is the boiling point of liquid nitrogen. When the raw material to be pulverized at a temperature lower than −196° C. is pulverized, the raw material to be pulverized is pulverized by repeating brittle fracture of the raw material to be pulverized. As a result, even when a uniaxially oriented liquid crystal polymer is pulverized, for example, not only does the fracture progress on a plane approximately parallel to the axial direction of the molecular axis of the liquid crystal polymer, but also brittle fracture progresses along a plane intersecting the axial direction, so that a granular pulverized LCP can be obtained.

[0062] In the freeze-pulverization method of the present embodiment, the rotation speed of the freeze-pulverization is preferably 1800 rpm or more, more preferably 2000 rpm or more, and even more preferably 2500 rpm or more. By adopting such a rotation speed, it becomes easier to obtain a granular finely pulverized liquid crystal polymer having a desired aspect ratio.

[0063] In the pulverization step of this embodiment, the liquid crystal polymer, which has been granulated by brittle fracture in liquid nitrogen, is continuously subjected to impact with a medium or the like while in an embrittled state, so that a plurality of fine cracks are formed from the outer surface to the inside of the liquid crystal polymer obtained in the pulverization step of this embodiment.

[0064] The granular finely pulverized LCP obtained by the fine pulverization process preferably has a D50 of 50 μm or less as measured by a particle size distribution measuring device using a laser diffraction scattering method, which can prevent the granular finely pulverized LCP from clogging the nozzle in the fiberization process described below.

[0065] (Coarse particle removal process: S13) Next, in the coarse particle removal step, coarse particles are removed from the granular pulverized LCP obtained in the pulverization step. For example, the granular pulverized LCP is sieved through a mesh to obtain granular pulverized LCP that falls below the sieve, and the granular liquid crystal polymer that remains above the sieve is removed to remove the coarse particles contained in the granular pulverized LCP. The type of mesh may be appropriately selected, and examples of the mesh include meshes with an opening of 53 μm. The method for producing a liquid crystal polymer powder according to this embodiment does not necessarily have to include the coarse particle removal step.

[0066] (Fiberization process: S14) Next, in the fiberization process, the granular liquid crystal polymer is crushed by a wet high-pressure crushing device to obtain a liquid crystal polymer powder. In the fiberization process, the finely pulverized LCP is first dispersed in a dispersion medium for the fiberization process. The finely pulverized LCP to be dispersed does not need to have coarse particles removed, but it is preferable that the coarse particles have been removed. Examples of the dispersion medium for the fiberization process include water, ethanol, methanol, isopropyl alcohol, toluene, benzene, xylene, phenol, acetone, methyl ethyl ketone, diethyl ether, dimethyl ether, hexane, or a mixture thereof.

[0067] Then, the finely pulverized LCP dispersed in the dispersion medium for the fiberization process, i.e., the finely pulverized LCP in a paste or slurry state, is passed through the nozzle under high pressure. By passing through the nozzle at high pressure, the shear force or collision energy due to the high-speed flow in the nozzle acts on the liquid crystal polymer, and the granular finely pulverized LCP is crushed, so that the fiberization of the liquid crystal polymer progresses, and a liquid crystal polymer powder that can be used in the manufacturing method of a liquid crystal polymer film can be obtained. From the viewpoint of applying a high shear force or high collision energy, it is preferable that the nozzle diameter of the nozzle is as small as possible within a range in which the finely pulverized LCP does not clog the nozzle. Since the particle diameter of the granular finely pulverized LCP in this embodiment is relatively small, the nozzle diameter in the wet high-pressure crushing device used in the fiberization process can be made small. The nozzle diameter is, for example, 0.2 mm or less.

[0068] In this embodiment, as described above, a plurality of fine cracks are formed in the granular pulverized LCP powder. Therefore, the dispersion medium penetrates into the inside of the pulverized LCP through the fine cracks by pressurization in the wet high-pressure crushing device. Then, when the paste-like or slurry-like pulverized LCP passes through the nozzle and is placed under normal pressure, the dispersion medium that penetrates into the inside of the pulverized LCP expands in a short time. The expansion of the dispersion medium that penetrates into the inside of the pulverized LCP causes destruction to proceed from the inside of the pulverized LCP. Therefore, fiberization proceeds to the inside of the pulverized LCP, and the liquid crystal polymer molecules are separated into domain units in which they are aligned in one direction. Thus, in the fiberization process in this embodiment, by defibrating the granular pulverized LCP obtained in the fine grinding process in this embodiment, a liquid crystal polymer powder having a lower content of aggregated particles and a fine fibrous form can be obtained, compared to the liquid crystal polymer powder obtained by crushing the granular liquid crystal polymer obtained by the conventional freeze grinding method.

[0069] In the fiberization step in this embodiment, the finely pulverized LCP may be crushed multiple times with a wet high-pressure crushing device to obtain a liquid crystal polymer powder.

[0070] <Method of manufacturing liquid crystal polymer film> As shown in FIG. 6, the method for producing a liquid crystal polymer film according to this embodiment includes a dispersing step (S21), a matting step (S22), a hot pressing step (S23), and a metal foil removing step (S24).

[0071] (Dispersion process: S21) In the dispersion step, which is the first step of the method for producing a liquid crystal polymer film, the liquid crystal polymer powder is dispersed in a dispersion medium to form a paste or slurry. In this manner, in this embodiment, the liquid crystal polymer powder in the form of fine fibers is used, so that the liquid crystal polymer powder can be dispersed in a dispersion medium with high viscosity. As a result, a homogeneous liquid crystal polymer film can be produced.

[0072] The dispersion medium used in the dispersion step includes water, terpineol, ethanol, and mixtures thereof. For example, when terpineol is used as the dispersion medium, a paste-like liquid crystal polymer powder is obtained. When a mixture of ethanol and water is used as the dispersion medium, a slurry-like liquid crystal polymer is obtained.

[0073] (Matting process: S22) Next, in the matting step, the liquid crystal polymer powder in the paste or slurry form is dried to form a liquid crystal polymer fiber mat. In one embodiment of the present invention, the matting step includes, for example, a coating step and a drying step.

[0074] In the coating process, the liquid crystal polymer powder paste is applied to a metal foil such as a copper foil. In the coating process, the liquid crystal polymer powder paste is applied to a metal foil such as a copper foil as described above, but instead of the metal foil, a polyimide film, a PTFE (polytetrafluoroethylene) film, or a composite sheet made of a reinforcing material such as a glass fiber fabric and a heat-resistant resin may be used. This makes it easy to industrially produce the liquid crystal polymer film.

[0075] Next, in a drying step, the paste-like liquid crystal polymer applied to the copper foil is heated and dried to evaporate the dispersion medium. The dispersion medium may be evaporated by suction. By the above heating and drying, a liquid crystal polymer fiber mat is formed on the metal foil such as the copper foil.

[0076] In addition, in the drying process, the dispersion medium is gradually removed from the paste-like liquid crystal polymer powder, so the overall thickness of the paste-like liquid crystal polymer powder gradually becomes thinner during drying. Therefore, the thickness of the liquid crystal polymer fiber mat becomes thinner than the overall thickness of the paste-like liquid crystal polymer formed on the copper foil. Specifically, in this embodiment, the overall thickness of the paste-like liquid crystal polymer powder is about 700 μm, and the thickness of the liquid crystal polymer fiber mat is, for example, about 150 μm.

[0077] Furthermore, as the overall thickness of the paste-like LCP powder gradually decreases during drying, the longitudinal direction of the fibrous particles in the LCP powder changes. Specifically, among the fibrous particles, those having a longitudinal direction along the overall thickness direction of the paste-like liquid crystal polymer powder tilt so that their longitudinal direction faces the in-plane direction of the copper foil. Therefore, the longitudinal direction of the fibrous particles in the formed liquid crystal polymer fiber mat is anisotropic.

[0078] In the matting step, a liquid crystal polymer paste may be applied to the liquid crystal polymer fiber mat formed on the metal foil by the drying step, and then the paste may be dried to evaporate the dispersion medium. In this manner, the matting step may include a coating step and a drying step repeated in this order. This allows a liquid crystal polymer fiber mat having a desired basis weight to be obtained.

[0079] The liquid crystal polymer fiber mat in this embodiment is formed by entangling fibrous particles of the liquid crystal polymer powder with each other. The liquid crystal polymer fiber mat has voids between the liquid crystal polymer powder particles. As described above, the longitudinal direction of the fibrous particles in the liquid crystal polymer powder is generally inclined toward the in-plane direction of the copper foil, so that the void ratio of the liquid crystal polymer fiber mat tends to be relatively large compared to the liquid crystal polymer mat obtained by matting the conventional liquid crystal polymer powder that does not contain fibrous particles. The void ratio is, for example, 80% to 90%.

[0080] In the matting process in this embodiment, instead of the coating process and drying process, a liquid crystal polymer powder in a paste or slurry form may be formed into a liquid crystal polymer fiber mat by a papermaking method. According to the papermaking method, it is not necessary to use a special dispersion medium (e.g., expensive terpineol) used in the coating process. In addition, in the papermaking method, the dispersion medium used in the dispersion process can be recovered and reused. In this way, the liquid crystal polymer film can be produced at low cost by the papermaking method.

[0081] In the mat-making process using the papermaking method, specifically, first, a liquid crystal polymer powder in a paste or slurry form is papered onto a mesh, a nonwoven microporous sheet, or a woven fabric, and then the liquid crystal polymer paste or slurry form arranged on the mesh is heated and dried to obtain a liquid crystal polymer fiber mat.

[0082] (Hot pressing process: S23) Next, in the hot pressing step, the liquid crystal polymer fiber mat is hot pressed to obtain a liquid crystal polymer film. Specifically, in the hot pressing step, the liquid crystal polymer fiber mat is hot pressed together with copper foil. As a result, the hot pressing step also serves as a step of bonding the liquid crystal polymer film and the copper foil to each other, so that a liquid crystal polymer film in a state in which the copper foil is bonded can be obtained at low cost. In addition, when heating is performed for a long time in the hot pressing step, it is preferable to vacuum hot press the liquid crystal polymer fiber mat. Furthermore, in the hot pressing step, a preliminary press may be performed at a temperature of 220°C or less before performing the vacuum hot pressing. By performing the preliminary press, the density of the fiber mat can be increased, and the coefficient of linear expansion (CTE) of the liquid crystal polymer film can be reduced. The density of the fiber mat is preferably 0.1 to 1.5 g / cm. 3 and more preferably 0.3 to 1.4 g / cm 3 It is.

[0083] In the hot pressing step, the hot pressing is preferably performed at a temperature about 5°C to 15°C lower than the melting point of the liquid crystal polymer constituting the liquid crystal polymer powder. If the hot pressing is performed at a temperature about 5°C to 15°C lower than the endothermic peak temperature, the sintering of the liquid crystal polymers is facilitated.

[0084] In addition, in the hot pressing process, a release film such as a polyimide film, a PTFE film, or a composite sheet made of a reinforcing material such as a glass fiber fabric and a heat-resistant resin may be sandwiched between the press used in the hot pressing process and the liquid crystal polymer fiber mat.

[0085] Alternatively, instead of the polyimide film, an additional copper foil may be sandwiched between the press and the liquid crystal polymer fiber mat. In this case, a liquid crystal polymer film having copper foil bonded to both sides can be obtained. The liquid crystal polymer film having copper foil bonded to both sides can be used as a double-sided copper-clad FCCL.

[0086] The outer dimensions of the liquid crystal polymer film formed by the hot pressing process in the thickness direction, i.e., the planar dimensions along the film surface, are approximately the same as those of the liquid crystal polymer fiber mat before the hot pressing. Then, by the hot pressing, the fibrous particles of the liquid crystal polymer powder in the liquid crystal polymer fiber mat, which have a longitudinal direction along the thickness direction of the liquid crystal polymer fiber mat, are heated while being pressed down in the in-plane direction of the copper foil. Since the liquid crystal polymer constituting the liquid crystal polymer powder has a molecular axial direction in the longitudinal direction of the fibrous particles, the axial direction of the liquid crystal polymer molecules is also pressed down in the in-plane direction of the copper foil. Therefore, except for the molecules constituting the clumped particles, the axial direction of each of the molecules constituting the liquid crystal polymer is oriented along the in-plane direction of the liquid crystal polymer film across the thickness direction of the liquid crystal polymer film. Therefore, in the formed liquid crystal polymer film, the main orientation direction of the liquid crystal polymer molecules tends to be along the in-plane direction of the copper foil, i.e., the in-plane direction of the liquid crystal polymer film.

[0087] It is believed that this is the reason why the in-plane linear expansion coefficient of the liquid crystal polymer film of this embodiment is reduced. Note that a liquid crystal polymer film having a low in-plane linear expansion coefficient has the advantage of being excellent in dimensional stability. In addition, when copper foil is laminated to the liquid crystal polymer film, it is possible to reduce the linear expansion coefficient of the liquid crystal polymer film to be approximately the same as the linear expansion coefficient of the copper foil (about 18 to 20 ppm / ° C.), which can suppress defects such as warping due to thermal shrinkage in the liquid crystal polymer film laminated with the copper foil.

[0088] Furthermore, the liquid crystal polymer powder in the liquid crystal polymer fiber mat may be bonded to each other while the fibrous particles remain entangled with each other. As a result, the liquid crystal polymer in the liquid crystal polymer film has a structure in which each molecule is entangled with each other. In addition, since the fibrous particles have a larger surface area than a spherical liquid crystal polymer having the same volume, the bonding area when the liquid crystal polymer powder is bonded to each other by the hot pressing process is also larger. As a result, the toughness and folding strength of the liquid crystal polymer film according to this embodiment are improved. In addition, the thickness of the liquid crystal polymer film is thinner than that of the liquid crystal polymer fiber mat by the hot pressing process.

[0089] In addition, the liquid crystal polymer mat obtained by matting the conventional liquid crystal polymer powder not containing the above-mentioned fibrous particles does not contain fibrous particles having the molecular axis direction in the longitudinal direction. Therefore, even if such a liquid crystal polymer mat is hot-pressed, the axial direction of the molecules constituting the liquid crystal polymer in the liquid crystal polymer film is not pushed down. Therefore, even if a liquid crystal polymer film is produced using a conventional liquid crystal polymer powder not containing fibrous particles, the main orientation direction of each of the molecules constituting the liquid crystal polymer does not follow the in-plane direction of the liquid crystal polymer film.

[0090] In addition, even if the liquid crystal polymer fiber mat obtained by matting the conventional liquid crystal polymer powder not containing fibrous particles is heat-pressed, the bonding area when the liquid crystal polymer powder particles are bonded to each other is extremely small. Therefore, when an external force is applied to a liquid crystal polymer film manufactured using a conventional liquid crystal polymer powder not containing fibrous particles, stress is concentrated at the bonding portion between the liquid crystal polymer powder particles. And, since the bonding area of ​​the bonding portion is small, the liquid crystal polymer film is broken at the bonding portion when an external force is applied. Thus, the liquid crystal polymer film manufactured using a conventional liquid crystal polymer powder not containing fibrous particles has a weak strength, and has low toughness and folding strength. The liquid crystal polymer film cannot be used as a substrate, a diaphragm, or a vibration damping plate for an FPC.

[0091] (Metal foil removal process: S24) Finally, if necessary, the metal foil bonded to the liquid crystal polymer film may be removed by etching, etc. This provides a liquid crystal polymer film free of the metal foil.

[0092] According to the manufacturing method of the liquid crystal polymer film of this embodiment, a liquid crystal polymer film can be manufactured using a liquid crystal polymer powder containing fibrous particles having an average aspect ratio of 10 or more and 500 or less and an average diameter of 2 μm or less, which was not possible to achieve in the past, thereby obtaining a liquid crystal polymer film with excellent folding strength, etc., which can be suitably used as a circuit board.

[0093] Conventionally, LCP films have been produced by melt extrusion, solution casting, and the like. In these methods, it was necessary to use an LCP (such as an LCP having an amide bond) that has a relatively low melting point and can be melted in the production equipment. In contrast, in the production method of the LCP film of the present embodiment, since it is not necessary to melt the LCP, an LCP with a high melting point as described above can be used. Therefore, for example, a liquid crystal polymer with a melting point of more than 330°C can be used, and a liquid crystal polymer film with excellent heat resistance containing a liquid crystal polymer with a melting point of more than 330°C can be produced.

[0094] <Method of manufacturing fiber mat> 7, the method for producing a fiber mat according to this embodiment includes a dispersion step (S31) and a mat-forming step (S32). The dispersion step (S31) is the same as the dispersion step (S21) in the method for producing a liquid crystal polymer film.

[0095] In the mat-forming step (S32), the liquid crystal polymer powder slurry is formed into a liquid crystal polymer fiber mat by a papermaking method. In the papermaking method, the dispersion medium used in the dispersion step can be recovered and reused, and the fiber mat can be produced at low cost.

[0096] 8 is a diagram showing an example of a matting step for matting the liquid crystal polymer powder in the manufacturing process of the fiber mat. With reference to FIG. 8, the matting step will be described in detail.

[0097] 8, the mat-forming step uses a papermaking machine 100. The papermaking machine 100 includes a supply roller 15 that supplies the microporous sheet 10, a take-up roller (not shown) that collects the microporous sheet 10, a papermaking wire 20, transport rollers 25 and 26, a storage section 40 that stores a dispersion medium 41 in which the liquid crystalline polymer powder is dispersed, a heating device 50, and a light irradiation device 60.

[0098] The papermaking wire 20 is, for example, a papermaking mesh of about 80 to 100 mesh. That is, the papermaking wire 20 has a pore size of about 150 μm to 180 μm. The papermaking wire 20 is transported by transport rollers 25 and 26 arranged in the transport direction. The transport roller 26 is disposed downstream of the transport roller 26. The papermaking wire 20 is transported by the transport rollers 25 and 26 so as to pass through the storage section 40.

[0099] The supply roller 15 supplies the microporous sheet 10 onto the papermaking wire 20. The microporous sheet 10 functions as a support for supporting the liquid crystalline polymer powder. The microporous sheet 10 placed on the papermaking wire 20 is transported by the papermaking wire 20 to pass through the storage section 40. The microporous sheet 10 that has passed through the storage section 40 is peeled off from the papermaking wire 20 and taken up by a take-up roller.

[0100] The microporous sheet 10 has a finer mesh than the papermaking wire 20. The microporous sheet 10 preferably has a mesh size of approximately 157 or more. In other words, the microporous sheet 10 preferably has a pore size of approximately 100 μm or less. This makes it possible to collect the fine liquid crystal polymer powder dispersed in the dispersion medium.

[0101] More preferably, the microporous sheet 10 has a pore size of about 5 μm to 50 μm. If the pore size of the microporous sheet 10 is too small, the drainage is poor and the time required for dehydration is long. On the other hand, if the pore size of the microporous sheet 10 is too large, it is difficult to collect the fine fibers (fine liquid crystal polymer powder), resulting in a poor yield.

[0102] When a microporous sheet 10 having a variation in pore size is selected, the texture of the formed fiber mat is affected, so when high uniformity is required for the fiber mat, a mesh that is periodically woven in a reticulated pattern is preferred. In other words, it is preferable to use a mesh for the microporous sheet 10 in which the pore size is uniform and the pores are not distributed unevenly.

[0103] For example, a woven mesh having a pore size of 50 μm or less can be used as the microporous sheet 10. As the woven mesh, for example, one made of synthetic fibers such as polyester can be used.

[0104] The microporous sheet 10 may have a basis weight of 15 g / m. 2 The following wet-laid nonwoven fabrics may be used. As the wet-laid nonwoven fabric, one made of microfibers may be used. The microfibers are made of synthetic fibers such as polyester.

[0105] The heating device 50 is disposed downstream of the storage section 40 in the conveying direction. The heating device 50 heats and dries the liquid crystal polymer powder 30 that has been woven onto the microporous sheet 10. As a result, a fiber mat is formed on the microporous sheet 10.

[0106] The light irradiation device 60 is disposed downstream of the heating device 50 in the conveying direction. The light irradiation device 60 irradiates light toward the fiber mat formed on the microporous sheet 10. The light irradiation device 60 may be, for example, a flash lamp.

[0107] The light irradiation device 60 preferably irradiates pulsed light. Since the pulsed light is absorbed by the surface (first main surface 31) of the fiber mat, the support (microporous sheet 10) supporting the fiber mat is not deteriorated by light irradiation. Therefore, a material having a lower melting point than the fiber mat can be used as the support, and the range of support options is expanded. In addition, since the fiber mat can be prevented from fusing to the support, the support can be reused repeatedly. As the light irradiation device 60, a light irradiation device (PulseForge (registered trademark) 1300 manufactured by NovaCentrix) can be used.

[0108] The mat-forming step (S32) includes a paper-making step, a peeling step, and a drying step, and may further include a light irradiation step. In the mat-forming step (S32), first, in a paper-making step, the dispersed liquid crystal polymer powder is papered into a microporous sheet 10. Specifically, the microporous sheet 10 supplied onto a papermaking wire 20 is conveyed by the papermaking wire 20 and passed through a storage section 40. At this time, the liquid crystal polymer powder dispersed in the dispersion medium 41 stored in the storage section 40 is papered into the microporous sheet 10.

[0109] Next, in a peeling step, the microporous sheet formed by weaving up the dispersed liquid crystal polymer powder is peeled off from the papermaking wire 20. Specifically, the microporous sheet 10 is wound up by a winding roller, thereby transporting the microporous sheet 10 in a direction different from that of the papermaking wire 20. The papermaking wire 20 may be transported in a direction different from that of the microporous sheet 10 by a transport roller 26.

[0110] Next, in a drying step, the liquid crystal polymer powder laid on the microporous sheet 10 is heated and dried by a heater 50. As a result, a fiber mat 30 made of the liquid crystal polymer is formed on the microporous sheet 10.

[0111] Next, in the light irradiation step, the first main surface 31 of the fiber mat 30 located on the opposite side to the side on which the microporous sheet 10 is located is irradiated with light. This causes the liquid crystal polymer powder located on the first main surface 31 side to fuse together. As a result, the strength of the fiber mat 30 is improved, and the fiber mat 30 can be carried to the next step without being damaged.

[0112] Furthermore, since only the liquid crystal polymer powder located in the surface layer on the first main surface 31 side is fused, the density of the entire fiber mat 30 is low, which makes it possible to ensure high breathability and high collection efficiency.

[0113] The fiber mat 30 after the light irradiation is placed on the microporous sheet 10 and then wound up by the winding roller in the winding process.

[0114] Fig. 9 is a diagram showing a step of irradiating the second surface of the fiber mat with light. As shown in Fig. 9, the mat-forming step may further include a step of peeling the fiber mat 30, the first main surface 31 of which has been irradiated with light, from the microporous sheet 10, and irradiating the second main surface 32 of the fiber mat 30 located on the opposite side to the side where the first main surface 31 is located with light. In this step, the fine fibers located on the second main surface 32 side are fused by light irradiation from a light irradiation device 61. The light irradiation device 61 may be the same as the light irradiation device 60 described above. When irradiating with light, the fiber mat 30 is irradiated while being transported.

[0115] When the liquid crystal polymer powder is fused on both the first main surface 31 side and the second main surface 32 side, the strength of the fiber mat 30 can be further improved.

[0116] Furthermore, when the fiber mat 30 is peeled off from the microporous sheet 10, since the liquid crystal polymer powder is fused on the first main surface 31 side and the fiber mat 30 has sufficient strength, the fiber mat 30 can be peeled off without damaging the fiber mat 30. The fiber mat 30 thus produced may be used as it is, or may be subjected to the hot pressing step S23 in the manufacturing method of a liquid crystal polymer film.

[0117] In this embodiment, light is irradiated to the fiber mat 30. When the liquid crystal polymer powder contained in the fiber mat contains a zirconium compound, the light absorption characteristics of the zirconium compound may increase the light irradiation efficiency. The increased light irradiation efficiency can improve the breaking tension of the fiber mat.

[0118] <<Method of processing liquid crystal polymer film and fiber mat>> In this embodiment, a liquid crystal polymer film and a fiber mat are irradiated with a laser to form a through hole or a cut portion. For the laser irradiation, a commercially available laser processing machine using, for example, a CO2 or semiconductor laser oscillator can be used. The beam spot diameter of the laser light can be changed by changing the lens of the laser processing machine. For fine processing, a small beam spot diameter is preferable.

[0119] When the liquid crystal polymer film or fiber mat contains a zirconium compound, the efficiency of laser irradiation is improved, making it easier to form through holes. EXAMPLES

[0120] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these.

[0121] <Example 1> (Production of liquid crystal polymer powder) In Example 1, first, pellets of uniaxially oriented liquid crystal polymer (cylindrical pellets with a diameter of 3 to 4 mm, melting point: 315°C, melt viscosity (MV): 17 Pa s) were prepared as the LCP raw material. The liquid crystal polymer material was a block copolymer of parahydroxybenzoic acid and 4,6-hydroxynaphthoic acid. The melt viscosity of the liquid crystal polymer (LCP raw material) could be adjusted by the polymerization temperature and polymerization time during polymerization of the copolymer.

[0122] The LCP raw material was coarsely pulverized using a cutter mill (MF10 manufactured by IKA). The coarsely pulverized liquid crystal polymer was passed through a 3 mm diameter mesh provided at the outlet of the cutter mill to obtain a coarsely pulverized liquid crystal polymer.

[0123] Next, the coarsely pulverized liquid crystal polymer was finely pulverized in a liquid nitrogen bead mill (LNM-08, manufactured by IMEX, vessel capacity: 0.8 L). Specifically, 400 mL of media and 30 g of the coarsely pulverized liquid crystal polymer were put into a vessel, and pulverization was performed for 120 minutes at a rotation speed of 2000 rpm. Zirconia (ZrO2) beads with a diameter of 5 mm were used as the media. In the liquid nitrogen bead mill, the coarsely pulverized liquid crystal polymer was dispersed in liquid nitrogen, and wet pulverization was performed. In this way, the coarsely pulverized liquid crystal polymer was pulverized in the liquid nitrogen bead mill to obtain granular finely pulverized LCP.

[0124] The particle size of this finely ground LCP was measured. In the particle size measurement, the finely ground LCP dispersed in the dispersion medium was subjected to ultrasonic treatment for 10 seconds, and then set in a particle size distribution measuring device (LA-950, manufactured by Horiba, Ltd.) using a laser diffraction scattering method, and the particle size was measured. As the dispersion medium, Ekinen (registered trademark, Japan Alcohol Sales Co., Ltd.), a mixed solvent mainly composed of ethanol, was used. The measured value of D50 of the finely ground LCP was 23 μm.

[0125] Next, the dispersion liquid obtained by dispersing the finely pulverized LCP in the equene was sieved through a mesh with an opening of 100 μm to remove the coarse particles contained in the finely pulverized LCP, and the finely pulverized LCP that passed through the mesh was collected. The yield of the finely pulverized LCP after removing the coarse particles was 85% by mass.

[0126] Next, the finely pulverized LCP from which the coarse particles had been removed was dispersed in a 20% by mass ethanol solution. The ethanol slurry in which the finely pulverized LCP was dispersed was repeatedly crushed five times using a wet high-pressure crushing device under conditions of a nozzle diameter of 0.2 mm and a pressure of 200 MPa, to form fibers. A high-pressure disperser (Nano-Veita manufactured by Yoshida Kikai Kogyo Co., Ltd.) was used as the wet high-pressure crushing device. As a result, a liquid crystal polymer powder dispersed in an ethanol aqueous solution was obtained.

[0127] (Melt viscosity measurement of liquid crystal polymer powder) Using a suction filtration device, the liquid crystal polymer powder dispersed in the ethanol aqueous solution was collected on a filter paper. The collected liquid crystal polymer powder was transferred to an evaporating dish and evaporated to dryness using a hot plate to obtain a dried liquid crystal polymer powder. The drying temperature was 80°C. The melt viscosity of the obtained dried liquid crystal polymer powder was measured.

[0128] The melt viscosity of the liquid crystal polymer powder was measured using a Capillograph manufactured by Toyo Seiki Seisakusho Co., Ltd. under the following measurement conditions in accordance with JIS K7199. Temperature: 340℃ Shear rate: 1000Sec -1 Capillary: Length 20mm / Diameter 1mm

[0129] At this time, the measured melt viscosity of the liquid crystal polymer powder was 15 Pa·s.

[0130] (Production of liquid crystal polymer films) First, a paste of the liquid crystal polymer powder was applied onto a copper foil and dried to form a liquid crystal polymer web (liquid crystal polymer fiber mat) on the copper foil.

[0131] Specifically, terpineol was added to the ethanol aqueous solution in which the liquid crystal polymer powder was dispersed, in an amount 20 times the mass of the dispersed liquid crystal polymer powder. The aqueous solution was then heated while being stirred, and the water and ethanol were evaporated and removed. This resulted in the liquid crystal polymer powder dispersed in terpineol. That is, the liquid crystal polymer powder was dispersed in terpineol, which is a dispersion medium, to form a paste.

[0132] Next, the liquid crystal polymer paste was applied onto the roughened surface of an electrolytic copper foil (FWJ-WS-12, manufactured by Furukawa Electric Co., Ltd.) having a thickness of 12 μm. The electrolytic copper foil on which the liquid crystal polymer paste powder was applied was heated to 130° C. on a hot plate to vaporize the terpineol, which was the dispersion medium, and dry the liquid crystal polymer paste powder on the electrolytic copper foil. In this way, a thin liquid crystal polymer fiber mat was formed on the electrolytic copper foil.

[0133] The liquid crystal polymer powder paste was further applied onto this thin liquid crystal polymer fiber mat. The applied liquid crystal polymer powder paste was dried in the same manner as the previously applied liquid crystal polymer paste was dried. By repeating the above application and drying several times, the basis weight was increased to 35 g / m. 2 A liquid crystal polymer fiber mat adjusted to have the above structure was formed on an electrolytic copper foil.

[0134] Next, the liquid crystal polymer fiber mat formed on the electrolytic copper foil was hot-pressed together with the electrolytic copper foil using a vacuum hot press (KVHC, manufactured by Kitagawa Seiki Co., Ltd.). Specifically, a release film was first laminated on the liquid crystal polymer fiber mat formed on the electrolytic copper foil on the side opposite to the electrolytic copper foil side. As the release film, a polyimide film (Kapton (registered trademark) 100H, manufactured by Toray DuPont Co., Ltd.) was used. Then, the liquid crystal polymer fiber mat laminated with the release film was set in the vacuum hot press at room temperature. The set liquid crystal polymer fiber mat was pressed together with the release film and the electrolytic copper foil at a pressure of 0.2 MPa, while being heated to 305°C at a rate of 7°C / min. After reaching 305°C, the liquid crystal polymer film was pressed together with the release film and the electrolytic copper foil at a pressure of 600 MPa while maintaining the temperature at 305°C. MPa The film was pressed for 5 minutes under the condition of 170 mm square. After the heat press, the release film was removed to obtain a liquid crystal polymer film formed on the electrolytic copper foil.

[0135] Finally, the electrolytic copper foil that had been bonded to the liquid crystal polymer film was removed by etching with an aqueous solution of ferric chloride. This resulted in the production of a liquid crystal polymer film. The thickness of the liquid crystal polymer film was 25 μm.

[0136] <Examples 2 to 9 and Comparative Example 1> In Examples 2 to 9 and Comparative Example 1, LCP pellets having melt viscosities of 23, 32, 35, 40, 47, 54, 63, 79, and 14, respectively, were used as raw materials (see Table 1). The melt viscosity of the liquid crystal polymer powder was changed by changing at least one of the polymerization temperature and polymerization time during polymerization. In other respects, the liquid crystal polymer powder was produced in the same manner as in Example 1, and a liquid crystal polymer film was obtained. The melt viscosities of the produced liquid crystal polymer powders were 20, 29, 33, 36, 45, 50, 60, and 77, respectively.

[0137] [Observation of liquid crystal polymer powder] 1(a) to (j) are photographs (scanning electron microscope images) of the liquid crystal polymer powders in Comparative Example 1 (MV=12), Example 1 (MV=15), Example 2 (MV=20), Example 3 (MV=29), Example 4 (MV=33), Example 5 (MV=36), Example 6 (MV=45), Example 7 (MV=50), Example 8 (MV=60) and Example 9 (MV=77). From the photograph in FIG. 1, it can be seen that the liquid crystal polymer powders of the examples contain fibrous particles that are thinner and longer (smaller fiber diameter and larger aspect ratio) than the liquid crystal polymer powders of the comparative examples.

[0138] [Measurement of bulk density of liquid crystal polymer powder] For each of the liquid crystal polymer powders according to Examples 1 to 9 and Comparative Example 1, the bulk density was measured. Specifically, first, a liquid crystal polymer powder was dispersed in a dispersion medium (20% by mass ethanol solution) to prepare a dispersion (solid concentration: 0.1% by mass). After thoroughly stirring the dispersion, it was left to stand in a graduated cylinder for 2 hours or more, and the volume of the liquid crystal polymer powder when the liquid crystal polymer powder had settled was read from the graduated cylinder scale, and the bulk density [mass / volume] was calculated from the measured volume and the mass of the liquid crystal polymer powder (amount blended in the dispersion). The measurement results of the bulk density of the liquid crystal polymer powder are shown in Table 1 and FIG.

[0139] [MIT folding fatigue test] An MIT folding fatigue test was performed using an MIT folding fatigue tester for each of the liquid crystal polymer films according to Examples 1 to 9 and Comparative Example 1. The test was performed on a test film having a width of 10 mm and a thickness of 25 μm taken from each liquid crystal polymer film under the conditions of a load of 500 g, a curvature radius of 0.2 mm, a bending angle of 135 degrees, and a speed of 175 cpm. The measurement results of the MIT folding endurance number of the liquid crystal polymer film are shown in Table 1 and FIG.

[0140] [Measurement of linear expansion coefficient] The in-plane linear expansion coefficient was measured for each of the liquid crystal polymer films according to Examples 1 to 9 and Comparative Example 1. Specifically, the in-plane (XY direction) linear expansion coefficient was measured for each of the liquid crystal polymer films by a TMA (thermomechanical analysis) method in accordance with JIS K 7197. The TMA conditions were a temperature rise from room temperature to 150° C. at a rate of 10° C. / min in a nitrogen atmosphere, a load of 10 g, and a rectangular sample shape (5 mm×15 mm). The measurement results of the coefficient of linear expansion (CTE) of the liquid crystal polymer film are shown in Table 1 and FIG.

[0141] [Table 1]

[0142] 3, the liquid crystal polymer films according to Examples 1 to 7, in which liquid crystal polymer powders having a melt viscosity of 15 to 77 Pa s (particularly 20 to 77 Pa s) were used, had MIT folding endurance of 100 or more, and showed improved folding endurance. Therefore, it was confirmed that these liquid crystal polymer films have sufficient flexibility for use as a base material for a flexible substrate or a diaphragm. Incidentally, it has been found that the MIT folding endurance of an LCP film produced in the same manner as in Example 1 using the fibril LCP described in Patent Document 1 is about 10 times, which is similar to that of the comparative example.

[0143] It can be seen from the results shown in Table 1 and Figure 2 that the bulk density of the liquid crystal polymer powder increases as the melt viscosity of the liquid crystal polymer powder increases. This is believed to be because the fibrous particles contained in the liquid crystal polymer powder become thinner and longer as the melt viscosity of the liquid crystal polymer powder increases. This is believed to have improved the folding endurance of the liquid crystal polymer film as described above.

[0144] Furthermore, from the results shown in Table 1 and FIG. 4, it can be seen that the liquid crystal polymer films of Examples 1 to 9, in which a liquid crystal polymer powder having a melt viscosity of 15 to 77 Pa·s was used, had a linear expansion coefficient of 20 or less. In addition, by using a liquid crystal polymer film having a linear expansion coefficient similar to that of copper foil (approximately 18 to 20 ppm / °C), such as the liquid crystal polymer films of Examples 1 to 9, defects such as warping due to thermal shrinkage can be suppressed in the liquid crystal polymer film to which the copper foil is bonded.

[0145] <Example 10> A liquid crystal polymer film of Example 10 was produced using the same raw materials as in Example 4. The only difference from Example 4 is that a preliminary pressing process was performed as a process before the liquid crystal polymer fiber mat formed on the electrolytic copper foil was hot-pressed together with the electrolytic copper foil using a vacuum high-temperature press device. The preliminary pressing process was performed by first pressing at room temperature (7 MPa, 10 sec) and then pressing at 200°C (7 MPa, 10 sec). Thereafter, the same treatment as in Example 4 was performed, specifically, a heat treatment was performed using a vacuum high-temperature press device (Kitagawa Seiki Co., Ltd., KVHC).

[0146] (evaluation) The density of the fiber mats of Examples 4 and 10 was measured by the following method. The coefficient of linear expansion (CTE) of the liquid crystal polymer film of Example 10 was measured by the same method as that of the liquid crystal polymer film of Example 4, and the MIT folding fatigue test was performed. The measurement results are shown in Table 2.

[0147] (Measurement of density of fiber mat) The density of the fiber mat was calculated by measuring the weight and thickness of the liquid crystal polymer fiber mat formed on the electrolytic copper foil. Specifically, the weight of the liquid crystal polymer fiber mat was calculated by subtracting the weight of the electrolytic copper foil from the measured weight. The thickness was measured using a micro gauge.

[0148] [Table 2]

[0149] From the results shown in Table 2, it can be seen that the density of the fiber mat is increased by performing the preliminary pressing, and the coefficient of linear expansion (CTE) of the liquid crystal polymer film is reduced. By the preliminary pressing, among the fibrous particles of the liquid crystal polymer powder in the fiber mat, the fibrous particles having a longitudinal direction along the thickness direction of the liquid crystal polymer fiber mat are pushed down in the in-plane direction of the copper foil. Therefore, except for the molecules constituting the clumped particles, the axial direction of each of the molecules constituting the liquid crystal polymer is oriented along the in-plane direction of the liquid crystal polymer film across the thickness direction of the liquid crystal polymer film. Therefore, in the molded liquid crystal polymer film, the main orientation direction of the molecules of the liquid crystal polymer tends to be along the in-plane direction of the copper foil, that is, the in-plane direction of the liquid crystal polymer film. As a result, the CTE of the liquid crystal polymer film of this embodiment is reduced, and in the liquid crystal polymer film laminated with the copper foil, defects such as warping due to thermal shrinkage can be suppressed. In addition, it can be seen that the MIT folding endurance number can be improved by orienting the liquid crystal polymer film in the in-plane direction.

[0150] <Example 11, Comparative Example 2> (Production of fiber mats of Example 11 and Comparative Example 2) Using the liquid crystal polymer powder of Example 1 (melting point 315°C), a required amount of water and ethanol were added to prepare 2.2g of liquid crystal polymer powder per 30L of 50wt% ethanol aqueous solution, and the slurry liquid crystal polymer powder was formed into a fiber mat by a papermaking method. A square sheet machine 2555 manufactured by Kumagai Riki Co., Ltd. was used as the papermaking machine, and the liquid crystal polymer powder dispersed in the dispersion medium was papered on a microporous sheet of polyester mesh with a pore size of 11μm. Next, the fiber mat of Example 11 was formed on the microporous sheet by heating and drying at a temperature of 100°C using a hot air dryer. The basis weight of the fiber mat was 35g / m 2 That was about it.

[0151] The obtained fiber mat was peeled off from the microporous sheet and heat-treated in a N2 atmosphere for 1 hour at temperatures of 280°C, 320°C, and 360°C. An inert oven was used as the heating furnace.

[0152] The fiber mat of Comparative Example 2 was prepared in the same manner as the fiber mat of Example 11 using the liquid crystal polymer powder of Comparative Example 1 (melting point 315°C), and was subjected to heat treatment at temperatures of 280°C, 320°C, and 360°C in the same manner as the fiber mat of Example 11. The breaking tension of the fiber mats of Example 11 and Comparative Example 2 was measured by the following method. The measurement results are shown in Table 3.

[0153] (Measurement of breaking tension of fiber mat) The breaking tension was measured for the fiber mats of Example 11 and Comparative Example 2 that were heat-treated at each temperature. The breaking tension was measured using an autograph (AG-XDplus manufactured by Shimadzu Corporation) after processing the heat-treated fiber mat into a width of 20 mm and a length of 100 mm. The measurement conditions were a take-up speed of 0.33 mm / sec, mode: tension, and an initial length of 50 mm.

[0154] [Table 3]

[0155] From the results shown in Table 3, it was found that in Example 11, even if the heat treatment temperature was 280° C., which was below the melting point, a breaking tension of 0.8 N / 20 mm or more was obtained.

[0156] <Examples 12 and 13> (Production of fiber mats of Examples 12 and 13) When the content of zirconia in the total amount of the liquid crystal polymer powder is W (wt%), the content of zirconia W of the liquid crystal polymer powder of Example 1 was 0.0219 wt%. The content of zirconia W was calculated by the following method. When the liquid crystal polymer powder of Example 1 was subjected to a process for removing zirconia by the following method, the content of zirconia W calculated by the following method was 0.0005 wt%.

[0157] Using the liquid crystal polymer powder of Example 1 (without zirconia removal treatment, with zirconia removal treatment), fiber mats of Example 12 (prepared using liquid crystal polymer powder without zirconia removal treatment) and Example 13 (prepared using liquid crystal polymer powder with zirconia removal treatment) were prepared in the same manner as in Example 11. Instead of the heat treatment of Example 11, a light irradiation treatment was performed on the entire surface of the fiber mat using a light irradiation device (NovaCentrix, PulseForge (registered trademark) 1300) with a set voltage of 230V, 250V, and 270V for 3.5msec with a table height of 10mm.

[0158] (Method for measuring residual zirconia amount) 40 g of the liquid crystal polymer powder to be measured was dispersed in 500 mL of 1 mol% aqua regia and allowed to stand for 10 minutes. The powder and solution were separated by suction filtration. The filtered solution was measured using an ICP optical emission spectrometer (ICPS-8100, Shimadzu Corporation) to confirm whether it could be detected above the detection limit. The standard solution for the calibration curve was prepared using ICP standard 1000 mg / L Ceriptur (Merck). Standard solutions for the calibration curve were prepared at 0, 0.25, 0.50, 1.0, and 2.0 mg / L. The measurement conditions for the ICP optical emission spectrometer were twin sequential type, high frequency output 1.2 kW, plasma gas flow rate 14 L / min, auxiliary gas flow rate 1.2 L / min, carrier gas flow rate 0.7 L / min, nebulizer coaxial type, and measurement direction horizontal. The detection limit was set to 0.02 μg / L or less. The zirconium content per weight of the liquid crystal polymer powder was calculated from the concentration of the ICP solution using the following formula, where the amount of Zr (molecular weight 91) was converted into the amount of ZrO2 (zirconia) (molecular weight 123). W (weight%) = (zirconium ion concentration of measured solution (g / L)) × (123 ÷ 91) × 0.5 L ÷ 40 g × 100

[0159] (Method of removing zirconium) 40 g of the liquid crystal polymer powder was dispersed in 500 mL of 1 mol% aqua regia and left to stand for 10 minutes. The powder and solution were separated by suction filtration, and the powder alone was dispersed in 500 mL of pure water. The dispersed powder was again separated by suction filtration. This process was repeated three times, and the mixture was heated to 100°C on a hot plate to evaporate the water, producing a liquid crystal polymer powder from which the zirconia had been removed.

[0160] (evaluation) (Measurement of breaking tension) The breaking tension of the fiber mats of Examples 12 and 13 after the light irradiation treatment was measured by the above-mentioned method. The measurement results are shown in Table 4.

[0161] [Table 4]

[0162] The results shown in Table 4 show that, compared with Example 13, Example 12 gave a fiber mat with a higher breaking tension.

[0163] (Laser processability) After light irradiation, the fiber mats of Examples 12 and 13 (with a set voltage of 230 V for light irradiation treatment) were irradiated with a laser under the following conditions to perform laser processing. A KrF excimer laser with a wavelength of 248 nm was generated by a CoMPexPro series (manufactured by Coherent Corporation), and the generated laser was focused into an area of ​​1 mm square by a reflecting lens and a focusing lens. The prepared film was placed at the focal length for focusing, and the energy per irradiation (pulse) was 150 mJ / mm 2 The laser energy was set so that the energy was 7 irradiations (pulses). By this laser processing, through holes were opened in the fiber mat of Example 12, and the fiber mat of Example 13 was cut, although no through holes were opened. From the above results, it was found that the fiber mat of Example 12, which did not undergo the zirconia removal treatment, could be laser processed more efficiently.

[0164] In the above description of the embodiments, configurations that can be combined may be combined with each other.

[0165] The embodiments and examples disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not the above description, and is intended to include all modifications within the meaning and scope of the claims.

[0166] <1> A liquid crystal polymer powder containing fibrous particles made of a liquid crystal polymer, The liquid crystal polymer powder has a melt viscosity of 15 to 77 Pa·s. <2> The liquid crystal polymer powder has a melt viscosity of 20 to 77 Pa s. <1> The liquid crystal polymer powder according to claim 1. <3> When a fiber mat is formed using the liquid crystal polymer powder and heat-treated at a temperature below the melting point of the liquid crystal polymer powder, the fiber mat has a breaking tension of 1.0 N / 20 mm or more. <1> or <2> The liquid crystal polymer powder according to claim 1. <4> Further comprising a zirconium compound, <1> ~ <3> 13. The liquid crystal polymer powder according to claim 12, <5> The zirconium compound is contained in an amount of 0.001% by weight or more and 0.1% by weight or less based on the total amount of the liquid crystal polymer powder. <4> The liquid crystal polymer powder according to claim 1. <6> a fine pulverization step of pulverizing the liquid crystal polymer raw material while it is dispersed in liquid nitrogen to obtain a granular finely pulverized liquid crystal polymer; A fiberization step of crushing the finely pulverized liquid crystal polymer with a wet high-pressure crushing device to obtain a liquid crystal polymer powder, The method for producing a liquid crystal polymer powder, wherein the liquid crystal polymer raw material has a melt viscosity of 15 to 79 Pa·s. <7> The melt viscosity of the liquid crystal polymer raw material is 20 to 79 Pa s. <6> A method for producing the liquid crystal polymer powder according to claim 1. <8> The liquid crystal polymer raw material is a pellet made of a liquid crystal polymer. <6> or <7> A method for producing the liquid crystal polymer powder according to claim 1. <9> In the fine pulverization step, the liquid crystal polymer raw material dispersed in the liquid nitrogen is pulverized using media. <6> ~ <8> 13. A method for producing a liquid crystal polymer powder according to claim 12. <10> The melting point of the liquid crystal polymer raw material is higher than 300°C; The method further includes a coarse pulverization step of coarsely pulverizing the liquid crystal polymer raw material prior to the fine pulverization step. <6> ~ <9> 13. A method for producing a liquid crystal polymer powder according to claim 12. <11> <6> ~ <10> A liquid crystal polymer powder obtained by the production method described in any one of the above. <12> A liquid crystal polymer film comprising a liquid crystal polymer powder, A liquid crystal polymer film with an MIT folding resistance of 100 or more times. <13> The in-plane linear expansion coefficient of the liquid crystal polymer film is 20 ppm / °C or less; <12> The liquid crystal polymer film according to claim 1. <14> A fiber mat containing a liquid crystal polymer powder, the fiber mat having a breaking tension of 1.0 N / 20 mm or more when heat-treated at a temperature equal to or lower than the melting point of the liquid crystal polymer powder. <15> The density of the fiber mat is 0.1 to 1.5 g / cm 3 That is, <14> The fiber mat according to claim 1. <16> <1> ~ <5> and <11> A dispersing step of dispersing the liquid crystal polymer powder according to any one of the above in a dispersion medium to form a paste or a slurry; a matting step of drying the liquid crystal polymer powder in a paste or slurry form to form a liquid crystal polymer fiber mat; and a hot pressing step of hot pressing the liquid crystal polymer fiber mat to obtain a liquid crystal polymer film. <17> The mattification step includes a coating step of coating the liquid crystal polymer powder in a paste or slurry form on a copper foil. <16> 2. A method for producing a polymer film according to claim 1 . <18> In the hot pressing step, the liquid crystal polymer fiber mat is hot pressed together with the copper foil. <17> 2. A method for producing the liquid crystal polymer film according to claim 1 . <19> The process further includes a step of performing a pre-press at a temperature of 220 ° C. or less before the hot pressing step. <16> ~ <18> 13. A method for producing a liquid crystal polymer film according to claim 12. <20> In the mat-forming step, the liquid crystal polymer powder in a paste or slurry form is formed into the liquid crystal polymer fiber mat by a papermaking method; <16> ~ <19> 13. A method for producing a liquid crystal polymer film according to claim 12. <21> <16> ~ <20> 1. A liquid crystal polymer film obtained by the manufacturing method according to any one of the above. [Explanation of symbols]

[0167] 10 microporous sheet, 15 supply roller, 20 papermaking wire, 25, 26 transport rollers, 30 fiber mat, 31 first main surface, 32 second main surface, 40 storage section, 41 dispersion medium, 50 heating device, 60 light irradiation device, 100 papermaking machine.

Claims

1. A liquid crystal polymer powder containing fibrous particles made of a liquid crystal polymer, The liquid crystal polymer powder has a melt viscosity of 15 to 77 Pa·s; The liquid crystal polymer powder has an average fiber diameter of the fibrous particles of 1.2 to 1.8 μm.

2. 2. The liquid crystal polymer powder according to claim 1, wherein the liquid crystal polymer powder has a melt viscosity of 20 to 77 Pa·s.

3. The liquid crystal polymer powder according to claim 1 or 2, wherein when a fiber mat is formed using the liquid crystal polymer powder and heat-treated at a temperature below the melting point of the liquid crystal polymer powder, the breaking tension of the fiber mat is 1.0 N / 20 mm or more.

4. The liquid crystal polymer powder according to claim 1 or 2, further comprising a zirconium compound.

5. The liquid crystal polymer powder according to claim 4, wherein the zirconium compound is contained in an amount of 0.001% by weight or more and 0.1% by weight or less based on the total amount of the liquid crystal polymer powder.

6. a fine pulverization step of pulverizing the liquid crystal polymer raw material while it is dispersed in liquid nitrogen to obtain a granular finely pulverized liquid crystal polymer; A fiberization step of crushing the finely pulverized liquid crystal polymer with a wet high-pressure crushing device to obtain a liquid crystal polymer powder, The method for producing a liquid crystal polymer powder, wherein the liquid crystal polymer raw material has a melt viscosity of 15 to 79 Pa·s.

7. The method for producing a liquid crystal polymer powder according to claim 6, wherein the liquid crystal polymer raw material has a melt viscosity of 20 to 79 Pa·s.

8. The method for producing a liquid crystal polymer powder according to claim 6 or 7, wherein the liquid crystal polymer raw material is a pellet made of a liquid crystal polymer.

9. 8. The method for producing a liquid crystal polymer powder according to claim 6, wherein in the fine pulverization step, the liquid crystal polymer raw material dispersed in the liquid nitrogen is pulverized using media.

10. The melting point of the liquid crystal polymer raw material is higher than 300° C., The method for producing a liquid crystal polymer powder according to claim 6 or 7, further comprising a coarse pulverization step of coarsely pulverizing the liquid crystal polymer raw material prior to the fine pulverization step.

11. A liquid crystal polymer powder obtained by the method according to claim 6 or 7.

12. A liquid crystal polymer film comprising the liquid crystal polymer powder according to claim 1 or 2, A liquid crystal polymer film having an MIT folding endurance of 100 or more times.

13. 13. The liquid crystal polymer film according to claim 12, wherein the liquid crystal polymer film has an in-plane linear expansion coefficient of 14.1 to 20.0 ppm / °C.

14. A fiber mat comprising the liquid crystal polymer powder according to claim 1 or 2, wherein the breaking tension of the fiber mat is 1.0 N / 20 mm or more when heat-treated at a temperature below the melting point of the liquid crystal polymer powder.

15. The density of the fiber mat is 0.1 to 1.5 g / cm 3 15. The fiber mat of claim 14, wherein

16. A dispersing step of dispersing the liquid crystal polymer powder according to claim 1 in a dispersion medium to form a paste or a slurry; a matting step of drying the liquid crystal polymer powder in a paste or slurry form to form a liquid crystal polymer fiber mat; and a hot pressing step of hot pressing the liquid crystal polymer fiber mat to obtain a liquid crystal polymer film.

17. The method for producing a polymer film according to claim 16 , wherein the mattifying step includes a coating step of coating the liquid crystal polymer powder in a paste or slurry form onto a copper foil.

18. The method for producing a liquid crystal polymer film according to claim 17, wherein in the hot pressing step, the liquid crystal polymer fiber mat is hot pressed together with the copper foil.

19. The method for producing a liquid crystal polymer film according to any one of claims 16 to 18, further comprising a step of performing pre-pressing at a temperature of 220°C or less before the hot pressing step.

20. The method for producing a liquid crystal polymer film according to any one of claims 16 to 18, wherein in the matting step, the liquid crystal polymer powder in a paste or slurry form is formed into the liquid crystal polymer fiber mat by a papermaking method.

21. A liquid crystal polymer film obtained by the method according to any one of claims 16 to 18.

Citation Information

Patent Citations

  • Output level stabilizing system

    JP1984004307A

  • Polyalkylene arylate resin composition

    JP1993125160A

  • Thermoplastic liquid crystal polymer film and circuit board using the same

    JP2018109090A

  • Liquid crystal polymer film and method for producing same

    WO2021177402A1